TERRITORIALITY IN THE UTILIZATION OF POST-REVITALIZATION KAYUTANGAN CORRIDOR - Ramadhanty, Fakhita Aulia; Asikin, Damayanti; Santosa, Herry (Directorate of Research and Community Service (DRPM), 2025)
Kayutangan Street Corridor in Malang City is a historical area that has been revitalized since 2020, aiming to revive its identity as a heritage public space as well as a commercial corridor of the city. After revitalization, the area's pedestrian path has experienced an increase in function and activity, but it also raises new problems in the form of overlapping spatial use and territorial behavior by various user groups. This study aims to identify the pattern of utilization and territoriality of pedestrian paths formed in the Kayutangan corridor after revitalization. The method used is qualitative descriptive with data collection techniques in the form of placed centered mapping and photography surveys, which are carried out in three corridor distribution zones. The results of the study show that pedestrian paths are used not only for pedestrian mobility, but also social, informal economy, and cultural activities. It was found that there was an overlap of functions on the pedestrian path which eventually formed various kinds of territories, namely the primary territory by the owner of the shop/building, the secondary territory by informal traders, and the public territory by pedestrians and temporary visitors. This phenomenon indicates the existence of spatial conflicts and need for more inclusive space management. The conclusion of this study emphasizes the importance of managing public spaces that are sensitive to social dynamics so that the function of pedestrians as an inclusive urban space can be maintained.